Subsequent colic syndrome due to perirectal abscess in an equine model – Case report - Góss, Geórgia Camargo; Rodrigues, Cláudia Medeiros; Pozzobon, Ricardo; Prestes, Rafaela Silveira; Brandolt, Inácio Manassi Conceição; Machado, Ingrid Rios Lima; Scheffel, Brenda Strassburger; Klaus, Gustavo José; Duarte, Claudia Acosta (Medicina Veterinária, 2020)
Colic is the most frequent syndrome of equine digestive system, and impaction is the most common disease among its many etiologies. The small colon can suffer with intraluminal or extraluminal obstructions resulting from many causes. These obstructions present signs such as abdominal pain, poorly altered physiological parameters, dyskinesia and tenesmus. The aim of the present study is to describe a small colon impaction secondary to perirectal abscess in the pelvic musculature. The equine model was assisted at Veterinary University Hospital of Federal University of Pampa (Unipampa) and surgery was the therapy of choice; however, the animal ended up dying during anesthesia application. The ultimate diagnostic was provided by necropsy, which showed one abscess in the pelvic musculature, close to the terminal portion of the rectum. The relevance of the present study lies on the importance of using complementary diagnostic methods, as well as on the presentation of another cause of colic, which is little described in the literature. The present results allowed enhancing the prognostics and treatments applied to horses with this disease.